Augmenting the Effectiveness of CAR-T Cells by Enhanced Self-Delivery of PD-1-Neutralizing scFv - Ping, Yu; Li, Feng; Nan, Shufeng; Zhang, Daiqun; Shi, Xiaojuan; Shan, Jiqi; Zhang, Yi (Frontiers in Cell and Developmental Biology, 2020)
Chimeric antigen receptor T (CAR-T) cell therapy is not satisfying in solid tumors. PD-1-mediated suppression greatly hinders CAR-T cells in the microenvironment. It has been shown that PD-1 blockade improves the effectiveness of CAR-T cells. Herein, we designed CAR-T cells than could secret anti-PD-1 scFv by themselves. To obtain optimal secretions of scFv, we screened several signal peptides. And the segment from human increased the extracellular production of PD-1-neutralizing proteins. The secreted neutralizing scFv efficiently blocked PD-1 and enhanced T cell activation when PD-L1 was present. Further analysis showed that CAR-T cells themselves could secret anti-PD-1 scFv with bioactivity. In contrast to the prototype, the scFv-producing CAR-T cells demonstrated decreased PD-1 but increases expansion and toxicity against solid tumor cells. In the subcutaneous and orthotopic xenograft models, the self-delivered anti-PD-1 scFv increased CAR-T cell functionalities and tumor-suppressions. Our work suggested that engineering T cells to co-express antigen-responsive receptors and checkpoint inhibitors is effective to optimize CAR-T cell therapy for solid tumors.